Analisis Faktor Risiko Prediabetes Pada Remaja di STIKES Panakkukang Makassar - Malik, Muh Zukri; Atikah Asri Putri; Syamsuddin; Muh Yusuf Tahir; I Kade Wijaya (Caring : Jurnal Keperawatan, 2025)
Prediabetes occurs when someone has an excess glucose in their blood but not high enough to be called diabetes mellius. It is categorized as prediabetes when the impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) are defined. The aim of the research is to analyze the correlation between consuming sugar-sweetened beverages (SSBs), obesity, and physical activity with the occurrence of prediabetes in young adults at STIKes Panakkukang Makassar. The study employs the quantitative approach and the analytical survey method by using the cross-sectional design. The research subjects are 75 students of the second year (2022), who were selected by using proportional stratified random sampling. The prediabetes prevalence is measured based on the FBS measurement with glucometer. The consumption of SSBs is measured based on the additional sugar consumption per day. The obesity is measured by using body mass index. The physical activity refers to the Global Physical Activity Questionnaire (GPAQ). The data were analyzed by using Chi Square. The prediabetes prevalence was found 33.3%, consumed high SSBs was 61.3%, obesity was 84%, and lack of physical activity was 30.7%. The bivariate analysis of consuming SSBs (p=0.036) and physical activity (p=0.042) have shown the prevalence of prediabetes, whereas the obesity and the prediabetes prevalence had no correlation (p=0.519). Consuming the SSBs and physical activity have significant impact on the prediabetes prevalence, but there is no correlation with the obesity. It is important for the teenagers not to compromise their life style and perform more physical activities to control their blood sugar.